A Systematic Review and Meta-analysis on the Epidemiology of the Muscular Dystrophies. (24th November 2015) - Mah, Jean K.; Korngut, Lawrence; Fiest, Kirsten M.; Dykeman, Jonathan; Day, Lundy J.; Pringsheim, Tamara; Jette, Nathalie
Abstract: Background: The muscular dystrophies are a heterogeneous group of genetic muscle diseases with variable distribution of weakness and mode of inheritance. Methods: We previously performed a systematic review of worldwide population-based studies on Duchenne and Becker muscular dystrophies; the current study focused on the epidemiology of other muscular dystrophies using Medline and EMBASE databases. Two reviewers independently reviewed all abstracts, full-text articles, and abstracted data from 1985 to 2011. Pooling of prevalence estimates was performed using random-effect models. Results: A total of 1104 abstracts and 167 full-text articles were reviewed. Thirty-one studies met all eligibility criteria and were included in the final analysis. The overall pooled prevalence of combined muscular dystrophies was 16.14 (confidence interval [CI], 11.21-23.23) per 100, 000. The prevalence estimates per 100, 000 were 8.26 (CI, 4.99-13.68) for myotonic dystrophy, 3.95 (CI, 2.89-5.40) for facioscapulohumeral dystrophy, 1.63 (CI, 0.94-2.81) for limb girdle muscular dystrophy, and 0.99 (CI, 0.62-1.57) for congenital muscular dystrophies. Conclusions: The studies differed widely in their approaches to case ascertainment, and substantial gaps remain in the global estimates of many other types of muscular dystrophies. Additional epidemiological studies using standardized diagnostic criteria as well as multiple sources of case ascertainment will help address the economic impact and health care burden of muscular dystrophies worldwide. RÉSUMÉ: Revue systématique et méta-analyse de l'épidémiologie des dystrophies musculaires. Contexte: Les dystrophies musculaires constituent un groupe hétérogène de maladies musculaires génétiques ayant une distribution de la faiblesse et une hérédité variables. Méthode: Nous avons effectué antérieurement une revue systématique des études populationnelles du monde entier sur la dystrophie musculaire de Duchenne et celle de Becker. Cette étude, effectuée dans les bases de données Medline et EMBASE, cible l'épidémiologie d'autres dystrophies musculaires. Deux examinateurs indépendants ont revu tous les résumés, le texte intégral des articles et les données publiées de 1985 à 2011. Le regroupement des estimés de prévalence a été effectué au moyen de modèles à effets aléatoires. Résultats: En tout, 1104 résumés et 167 articles en texte intégral ont été revus. Trente et une études rencontraient tous les critères d'éligibilité et ont été incluses dans l'analyse finale. La prévalence globale des dystrophies musculaires combinées était de 16, 14 (intervalle de confiance [IC] de 11, 21 à 23, 23) par 100, 000 de population. Les estimés de prévalence par 100, 000 étaient de 8, 26 (IC : 4, 99 à 13, 68) pour la dystrophie myotonique, 3, 95 (IC : 2, 89 à 5, 40) pour la myopathie facio-scapulo-humérale, 1, 63 (IC : 0, 94 à 2, 81) pour la myopathie scapulo-humérale et 0, 99 (IC : 0, 62 à 1, 57) pour les dystrophies musculaires congénitales. Conclusions: Les études utilisaient des approches sensiblement différentes pour l'identification des cas et il existe des écarts considérables dans les estimés globaux de plusieurs autres types de dystrophies musculaires. D'autres études épidémiologiques utilisant des critères diagnostiques standardisés ainsi que de multiples sources d'identification des cas aideront à faire face à l'impact économique et au fardeau des soins de santé engendrés par les dystrophies musculaires à l'échelle mondiale.